Предмет:
МатематикаАвтор:
анонимУпростим выражение 2/(a + 2) - (a - 2)/(a^2 + 2 * a);
Приведем разность дробей к общей дроби.
2/(a + 2) - (a - 2)/(a^2 + 2 * a) = 2/(a + 2) - (a - 2)/(a * (a + 2)) = (2 * a - (a - 2) * 1)/(a * (a + 2)) = (2 * a - (a - 2))/(a * (a + 2)) = (2 * a - a + 2)/(a * (a + 2)) = (a + 2)/(a * (a + 2)) = 1/(a * 1) = 1/a;
В итоге получили, 2/(a + 2) - (a - 2)/(a^2 + 2 * a) = 1/а.
Автор:
squirtvx4zДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть